Erosion of carbonate-bearing sedimentary rocks may close the alkalinity budget of the Baltic Sea and support atmospheric CO2 uptake in coastal seas - Wallmann, Klaus; Diesing, Markus; Scholz, Florian; Rehder, Gregor; Dale, Andrew W.; Fuhr, Michael; Suess, Erwin (Frontiers in Marine Science, 2022)
High alkalinity values observed in coastal seas promote the uptake of CO2 from the atmosphere. However, the alkalinity budget of coastal areas and marginal seas is poorly understood, even though some of the recently observed alkalinity enhancement can be ascribed to riverine fluxes and anaerobic processes in shelf sediments. Here, we investigate the alkalinity budget of the Baltic Sea to identify previously unrecognized alkalinity sources. We quantify the generation of alkalinity and dissolved calcium (Ca) in this marginal sea applying simple mass balance calculations. Using this approach, we identify alkalinity and Ca sources of approximately 324 Gmol yr-1 and 122 Gmol yr-1, respectively, that cannot be ascribed to the riverine input. The magnitude of the Ca source suggests that a major fraction of the excess alkalinity (244 Gmol yr-1) is induced by the dissolution of calcium carbonate (CaCO3). A review of available field data shows that carbonate-bearing rocks at the coast and the seabed of the Baltic Sea are rapidly eroded and may provide sufficient CaCO3 to close the Ca budget. Hence, dissolution of eroded CaCO3 is the most likely source for the Ca enrichment observed in Baltic Sea water. This hypothesis is supported by mass accumulation rates of sediments derived from radioisotope data that are evaluated to derive a basin-wide rate of mud to muddy sand accumulation at the bottom of the Baltic Sea. The resulting value (139 Tg yr-1) exceeds current estimates of riverine particle fluxes into the Baltic Sea by more than one order of magnitude and confirms that rates of till erosion are sufficiently high to account for the Ca and most of the alkalinity excess in Baltic Sea water. Finally, we show that deliberate addition of CaCO3 to sediments deposited in the Baltic Sea could neutralize significant amounts of CO2 and help to achieve net-zero greenhouse gas emissions in the Baltic region.